Integrated cad and reverse engineering to enhance conception and design - Butt, Ahmed Tamkin; Siegkas, Petros (My University, 2021)
his paper details the adoption of a methodology of integrating CAD with reverse engineering to enhance the conception and design skills of first year engineering students. The students are given an engineered device to reverse engineer via physical deconstruction and redesign via CAD as a group. The aim of administering this methodology is two-fold; firstly, to ensure students from various engineering backgrounds (Mechanical, Electronic, Biomedical and Sport Engineering) reverse engineer devices relevant to their discipline and specifically work on CAD models of these devices to enhance relatability. Secondly, to ensure students appreciate and adopt the underpinning practices involved in the design and conception of engineering devices. As opposed to dictating specifications, the redesign of the device is left at the discretion of the students to encourage a student-centred approach whereby the students take on an active role in the learning process. Additionally, designing and deconstructing the same device as part of a group ensures higher student engagement. This paper demonstrates the efficacy of the adopted approach by providing various examples of students’ Reverse Engineering/CAD outputs as well as assessment statistics. The paper also details the online support provided in addition to the on-site teaching to aid optimum learning in a blended learning environment.
Keywords: CAD; engineering design; Introduction to engineering; reverse engineering; Standards: 1, 2, 3, 4, 6, 8, 11